Π^0_2 Subsets of Domain-Complete Spaces and Countably Correlated Spaces - Goubault-Larrecq, Jean (Topology Proceedings, 2020)
We show that every Π^0_2 subset of a domain-complete space is domain-complete. This implies that Ruiyuan Chen’s countably correlated spaces are all domain-complete (see Notes on quasi-Polish spaces. Available at arXiv:1809.07440v1 [math.LO]).